Pengaruh Beban Kerja, Lingkungan Kerja Fisik dan Komunikasi Interpersonal Terhadap Kepuasan Kerja Pada Karyawan PT. Tjipta Rimba Djaja Tanjung Mulia - Mario Simangungsong; Shofyan Roni (ProBisnis : Jurnal Manajemen, 2025)
This study aims to determine the effect of workload, physical work environment, and interpersonal communication on job satisfaction among employees of PT. Tjipta Rimba Djaja. This study employed a quantitative approach. The data sources used were primary and secondary data. The population consisted of 112 employees of PT. Tjipta Rimba Djaja. The sample size was 112 respondents. The sampling technique used in this study was saturated sampling. Data analysis techniques used in this study included descriptive statistics, classical assumption tests, multiple linear regression tests, and hypothesis testing. Based on the partial test results, it was found that workload has a positive and significant effect on employee satisfaction, with a t-test of 3.714 > t-table 1.981. Therefore, based on the partial test, H1 can be concluded as accepted. Furthermore, the work environment variable partially did not have a positive and significant effect on employee job satisfaction, with a t-value of 1.984 < t-table 1.981. Therefore, the partial test results concluded that H2 was rejected. Furthermore, interpersonal communication had a positive and significant effect on employee job satisfaction, with a t-value of 2.986 > t-table 1.981. Therefore, the partial test results concluded that H3 was accepted. Simultaneous results revealed that workload (X1), work environment (X2), and interpersonal communication (X3) collectively had a positive and significant effect on employee job satisfaction at PT. Tjipta Rimba Djaja.